The nature of organizational leadership : understanding the performance imperatives confronting today's leaders - Zaccaro, Stephen J.; Klimoski, Richard J. (Organizational frontiers series., 2002)
The quality of an organization's top leaders is a critical influence on its overall effectiveness and continuing adaptability. Yet, little current research examines leadership within the context of organizational structure, such as how leaders influence organizational performance in those key moments when an executive's action is critical to driving the organization forward. This book represents a significant contribution to the literature of leadership, combining a contextual approach to organizational leadership with an in-depth treatment of the cognitive, social, and affective dynamics unde.